INTERNATIONAL BUSINESS EXPANSION STRATEGY THROUGH AMAZON’S GLOBAL E-COMMERCE PLATFORM IN THE BEAUTY PRODUCT CATEGORY - Indaswari, Fidelia Dewi; Widia, Didi (Bisma: Jurnal Bisnis dan Manajemen, 2024)
In this modern age of rapid technological growth and abundant information, e-commerce has become a powerful tool for businesses looking to reach a global audience. Engaging in electronic commerce opens up a world of opportunity to tap into local and international markets ripe for expansion. This study aims to dig deeper into the beauty product preferences of the American populace, which uses Amazon to craft a strategic expansion plan that resonates with people's desires. This research delved into the realm of qualitative analysis by utilizing the innovative TOWS matrix analysis and STP analysis to uncover the desires and inclinations of individuals toward beauty products. To capture the attention of the Amazon e-commerce market, the company should target female consumers between the ages of 12 and 44 who are interested in vegan, eco-friendly products that are chemical-free, prioritize animal welfare, and are looking for high-quality decorative cosmetics. Furthermore, the company should promote eco-friendly products and professional makeup to cater to the growing demand for sustainable options among environmentally-conscious Americans. With a well-thought-out plan, the company has the potential to thrive and expand its business footprint by tapping into the endless possibilities of e-commerce platforms.